INTEGRATING POPULAR CULTURE IN THE LITERATURE CLASSROOM: BASIS FOR A TEACHING MODEL - Santos, Ramil Alejo; Nanquil, Luisito Manalansan (American International Journal of Social Science Research, 2023)
Popular culture’s integration with language lessons, particularly in literature lessons, is a practice already being employed by teachers. Earlier studies, both local and international, were already conducted, integrating pop culture references and materials in the literature classroom: memes, shows, music, games, among others, and groundworks about the approaches in teaching literature and different models in teaching exist but no studies have suggested a teaching model based on the integration of said variables. The current study tried to formulate a basis for a teaching model based on the integration of popular culture and literature lessons. English teachers at the secondary level, especially those who worked in public or private schools in Malolos, Bulacan, were asked how they incorporate pop culture into their literature classes, what challenges they face, and how they deal with them. The study utilized a qualitative ethnographic approach based on the etic perspective. For the investigation, a triangulation method was used. This includes evaluating the teacher-informants’ responses to the provided structured essay questions, conducting a focus group discussion, and comparing literature and studies on popular culture and literature instruction. The discussion sharing and the replies to the essay questions were compared to Weil and Joyce’s (1973) guidelines for a teaching model. The findings produced a model of teaching based on the specifications of environment, operation, procedure, and learning outcomes. JEL Classification Codes: G32, F65, L66, L25, M41.